MOTIVATIONS AND NEEDS IN THE MARKET ECONOMY - E.F. Diba,; S.B. Sartova,; T.V. Diba,; S.V. Gnezdilov, (Academic Journal of Physical and Chemical Sciences, 2019)
The human resource management system will not function properly unless an effective motivation model is developed. Over the entire period of the study of human behavior, scientists have put forward a large number of different theories that classify needs according to one or another of the criteria. It is important for the employee to feel his importance in front of the organization’s management and recognized ownership in its prosperity. An important role is played by the spirit of competition, the ability to work in a team, the possibility of self-realization and personal growth in the work process, pride in belonging to this organization, recognition of colleagues and management. One of the first behaviorists, from whose work leaders learned about the complexity of human needs and their impact on motivation, was Abraham Maslow. However, modern scientists have expanded the pyramid, adding aspects that meet the spirit of the times and reveal a new perspective on staff motivation.